Impacts of international studies on careers of Russian forestry graduates - Pishchuk, Ekaterina (SLU/Southern Swedish Forest Research Centre, 2009)
This study focuses on the differences in the career paths of the Russian graduates who have attended the Euroforester program and the graduates who have never studied abroad. It also deals with the questions of the education abroad impacts on the graduates’ careers. Previous studies focused only on the career paths of the graduates who attended the Euroforester program. It was also interesting to compare them with the Russian graduates who didn’t attend any programs abroad. Having sent a link to the online survey I got answers to the questions on professional identity, education, career, and job satisfaction. Data were analyzed with the help of the Excel program, besides, I used a statistical chi-square and Mann-Whitney U tests to find any statistical significance. The main result is that there’re differences in career paths, salary, and job satisfaction between two groups of the respondents. The Euroforesters have better job positions and bigger salaries than the Russian graduates. At the same time the Russian graduates are much more satisfied with their present jobs. There are almost no differences in professional identity of both groups. Most of them want Russian forests to be managed in nature-oriented way; they want forest to be state owned and think that there must be more environmental restrictions and control put on forest owners. As for the differences between genders, females get less salary and are not satisfied with it and the promotion opportunities. The conclusion is that education abroad has a great impact on career of graduates